(untitled) (INNOVATIVE ECONOMY, 2019)
Mazurenok O.R., Plekan U.M. SOCIAL AUDIT AS TOOL FOR ASSESSING CORPORATE SOCIAL RESPONSIBILITY Purpose. The aim of the article is to analyze the essence of social audit and realization of technologies of social audit of companies. Methodology of research. The foundation of this article is comprised of basic categories and concepts of social audit and steps in conducting social audit of companies. The dialectic approach is used in research to determine the cause-effect relationships, how they affect realization of social audit and what impact those social initiatives have on the main results of primary activity of companies in question. The basic criteria of organization of social activity of companies are determined in research due to the use of analysis methods and the indicators of social audit that reflect the state of the social sphere of companies are suggested. A big role in this was attributed to the methods of systematic structured analysis and synthesis to evaluate the tasks and functions of social audit, and a role in determining of its classification according to main characteristics. Findings. The article gives an in-depth explanation of essence and characteristics of social audit. The importance of social audit and its impact on the development of corporations and society at large are analyzed. The importance of social audit in the financial and economic systems as the main basis of the company economic interests is developed and the necessity of its introduction with the aim of establishing socially responsible economic activity of businesses is determined. A research of the development of social audit at the international level is conducted. The processes of social audit development and peculiarities of its formation in Ukraine are investigated. Its goal and functions are proved. The classification of social audit according to its main characteristics is given. The basic criteria of organization of social activity of companies are offered. Realization of technologies of social audit of companies is suggested on the basis of analyzed literary sources. Originality. The basic criteria of organization of social activity of companies are offered and the indicators of social audit that unlike the existing ones provide a better reflection of the state of the social sphere of companies are suggested. Practical value. Practical importance of the obtained results is in the possibility of using both scientific development findings and practical recommendations from the article for various domestic companies to elaborating efficient technologies of social audit for the development of socially responsible sphere of activity. Key words: social audit; control; corporate social responsibility; auditor’s report; social and economic system.